Empowering Youth: Socializing Drug Abuse Dangers in SMP Negeri 55 Makassar - Riri Amandaria; Saifuddin; Muhammad Aksha Wahda; Bahrul Amsal; Ulfa Utami Mappe (Paramacitra Jurnal Pengabdian Masyarakat, 2023)
The pervasive nature of drug abuse across various societal levels is deeply troubling, particularly its impact on students. Drugs, when introduced into the body, possess the ability to alter one's cognition and behaviour. This initiative is geared towards augmenting students' comprehension of drug varieties, associated risks, and effective preventive measures. The program took place at SMP Negeri 55 Makassar, utilizing lectures, discussions, and interactive Q&A sessions as its methodology. Engaging 58 students from the VIII and IX grades, this initiative was self-funded. The activity was executed successfully, eliciting a positive response, and achieving its intended objectives. There are plans for continual implementation in both the same and different locations to sustain this impactful service in the future.